Current Scenario of Maintenance 4.0 and Opportunities for Sustainability-Driven Maintenance - Suhas H. Sarje; Manoj A. Kumbhalkar; Dinesh N. Washimkar; Rajesh H. Kulkarni; Maheswar D. Jaybhaye; Wadhah Hussein Al Doori (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Industry 4.0, a shift from Industry 3.0, aims to enhance productivity and efficiency in operations and supply chain management. Maintenance plays a crucial role in this process, and IoT-enabled (Ind. 4.0) condition monitoring is a key component of this technology. However, challenges persist in implementing effective IoT-enabled condition monitoring solutions. The triple bottom line perspective (Economical, Ecological, and Social) is also crucial for realizing Ind. 4.0. This paper investigates the state of IoT-enabled industrial condition monitoring (Maintenance 4.0) and sustainability-driven maintenance (Maintenance 5.0), focusing on the challenges associated with implementing these concepts. The IoT-enabled technologies are divided into three layers: the application layer, the networking layer, and the physical layer. The physical layer, the lowest layer, faces numerous challenges in realizing maintenance 4.0 effectively. A new system configuration for vibration-based condition monitoring in an Ind. 4.0 environment is proposed to address these shortcomings. Wi-Fi technology is found to be the best option for high-throughput communication needs in the current scenario. The literature review reveals that while the economic aspect of maintenance 5.0 has been thoroughly examined, the environmental and social aspects have not been thoroughly assessed. Future research should focus on developing a new sustainable maintenance model that incorporates IoT-enabled technologies and investigates sustainable performance indicators to understand sustainability aspects quantitatively.